PENYERAPAN ZAT WARNA MALACHITE GREEN MENGGUNAKAN KULIT PISANG KEPOK (Musa balbisiana Colla) SEBAGAI BIOSORBEN DENGAN METODE BATCH - Riva Silvia; Edi Nasra; Budhi Oktavia; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2020)
Biosorption of Malachite green dyes using kepok banana peel (Musa balbisiana Colla) as a biosorbent has been carried out. The purpose of this study was to determine the optimum conditions for absorption of Malachite green by kepok banana peel biosorbent (Musa balbisiana Colla). The method used is the batch method. The variables tested were pH of the solution, concentration, particle size. The wavelength of Malachite green is 618 nm measured by the UV-Vis Spectrophotometer. The results showed that the optimum conditions for absorption occurred at pH 3, a concentration of 100 ppm, and a particle size of 150   μm with an absorption capacity of  8,6778 mg/g. The adsorption isotherm of Malachite green with kepok banana peel (Musa balbisiana Colla) biosorbent tends to follow the Freundlich isotherm with a determinant coefficient (R2) of 0.9996.